Examining Financial Sustainability in Investor-Backed vs. Independent Start-Ups: A Romanian Perspective - Paun , Dragos; Ienciu, Alin Ionel; Ienciu, Nicoleta Maria (Transformations In Business & Economics, 2025)
With the covid crisis the need for innovation in the health sector has increased substantially. At the same digitalization has started to play an important role in every industry. This current paper explores the financial performance of start-ups in Romania, with a particular focus on sustainability and the role of external investment. Through an empirical analysis of key financial metrics—including Return on Assets (ROA), Return on Equity (ROE), and Debt-to-Assets ratio—the research offers a comparative insight into the performance of companies with and without investors. Statistical tests, comprising t-tests and ANOVA, were employed to examine the differences in these metrics between the two groups of companies. The findings reveal no significant disparities in ROA, ROE, or the Debt-to-Assets ratio between investor-backed and non-investor-backed start-ups. This suggests that external investment does not inherently influence these financial indicators, with companies demonstrating comparable financial performance regardless of investor involvement. The research provides valuable implications for stakeholders, entrepreneurs, and policymakers interested in the sustainability and financial viability of start-ups in the Romanian entrepreneurial ecosystem.
Keywords: financial sustainability; return on equity; start-ups; entrepreneurship; MedTech